MENGGUGAT PERNIKAHAN DINI - Naufal (CENDEKIA: Jurnal Studi Keislaman, 2015)
The Marriage Act No. 1 of 1974 Article 2 paragraph (1), regulates that a legal marriage is a marriage conducted according to each religious law and belief. It stressed the rules concerning the minimum age limit for someone to be able to enter into marriage. The marriage issue is closely related to the population problem; the rate of population growth, following derivatives issue; health, housing, food and employment, and so on. Until now, marriage at an early age (under age-limit marriage) are still rampant in this country. While the population is still adhering to the tradition, although the Marriage Act has long been firmly set. This law stipulates that a person who wants to marry must have reached the age of 19 years for men and 16 years for women, and if not yet reached that age should get dispensation from the court. The regulation is for the benefit of both prospective spouses. Fostering households need their biological and psychological readiness in order to realize a good, eternal, and happy marriage,